2011
DOI: 10.1073/pnas.1107504108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assembly of physiological cohesin/DNA complexes

Abstract: Cohesin is a member of the Smc family of protein complexes that mediates higher-order chromosome structure by tethering different regions of chromatin. We present a new in vitro system that assembles cohesin-DNA complexes with in vivo properties. The assembly of these physiological salt-resistant complexes requires the cohesin holo-complex, its ability to bind ATP, the cohesin loader Scc2p and a closed DNA topology. Both the number of cohesin molecules bound to the DNA substrate and their distribution on the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
(76 reference statements)
3
23
0
Order By: Relevance
“…Cohesin located at centromeres appeared dependent on specific kinetochore proteins (28). Possibly in accordance with this notion, studies with crude S-phase yeast extracts reported cohesin loading onto specific pericentric DNA regions (29). The loaded cohesin was stably associated with this DNA (0.5 M KCl).…”
Section: Discussionsupporting
confidence: 63%
“…Cohesin located at centromeres appeared dependent on specific kinetochore proteins (28). Possibly in accordance with this notion, studies with crude S-phase yeast extracts reported cohesin loading onto specific pericentric DNA regions (29). The loaded cohesin was stably associated with this DNA (0.5 M KCl).…”
Section: Discussionsupporting
confidence: 63%
“…The structural basis through which cohesins maintain sister chromatid pairing remain controversial, but crystal structure analyses of highly conserved SMC complexes provide new insights into this important topic (Box 1). There is also clear evidence that cohesin subsets exhibit different and distinct chromatin-associated dwell times, supporting the notion that cohesin structures cycle between soluble pools and weakly or tightly bound chromatin complexes (Gause et al, 2010;Gerlich et al, 2006;McNairn and Gerton, 2009;Onn and Koshland, 2011). Ascertaining the extent to which altered cohesin conformations impact cohesion-DNA architecture may provide key insights into cohesin function in a wide variety of processes (Fig.…”
Section: Introductionmentioning
confidence: 81%
“…DNA sequences per se do not drive cohesin loading (Onn and Koshland, 2011; Murayama and Uhlmann, 2013). Instead, targeting likely depends on interactions between the loading complex and chromatin-associated factors.…”
Section: Discussionmentioning
confidence: 99%